MULTI-CRITERIA ANALYSIS AS A TOOL FOR MUNICIPAL PROPERTY MANAGEMENT - Daniela Constantin; Zizi Goschin; Statty Statev; Stela Raleva; Bogdan Ileanu (European Regional Science Association (ERSA), 2011)
In most decision making situations more than one criterion is involved and, as a consequence, confusion can arise if there is no logical and well structured decision-making process in place. The multi-criteria analysis (MCA) constitutes a tool that can help evaluate the relative importance of all criteria involved and reflect on their importance during project management and decision making. MCA is a management tool aiming at supporting decision makers faced with making numerous and conflicting evaluations by deriving a way to come to a compromise. This paper discusses the possibilities of applying MCA in the field of municipal property management, where the decision-makers have to find the most convenient destinations of municipal assets that can be used for various purposes such as: governmental, business, social use. In each case specific criteria and indicators are employed in the ranking and rating process, so as to get the corresponding weighted score. An application is also presented, as performed within a work package included in the project "Municipal Property Management in South- Eastern Cities (PROMISE)", aiming to develop a comprehensive system for municipal property classification for governmental use, social use and business use by means of criteria previously defined, processed by MCA operation. The resulted system is adapted to the strategic goals of the administrative authorities, contributing to an effective municipal property management by optimising and standardising the decision-making procedures. The framework created enables the municipalities to find an appealing combination between the use of properties for their own needs and for attracting investment and promoting sustainable development of their cities and regions. The project was initiated in 2009, being funded by the ERDF within the South-East Territorial Co-operation Programme.
Keywords: 330; multi-criteria analysis; criteria; indicators; ranking; municipal assets; strategic management